The roles of women in seed-sector development in South Sudan. - Subedi, Abishkar; Ngalamu, Tony; Uffelen, Gerrit-Jan van; Vernooy, Ronnie (2023)
This brief addresses two dimensions of women and seed systems development ̶ what women do for seed systems development, and what seed systems interventions could do for women ̶ in the context of South Sudan. In South Sudan, women play key roles in seed systems, as custodians and managers of seeds and seed related information, but these roles are not always recognized, respected, supported and rewarded. The brief proposes a number of seed interventions to empower farmers, with special attention paid to women.